Isolated arteritis of the epididymis. Issue 7 (July 1985) - Womack, C; Ansell, I D
Abstract : The clinical, histological, and immunohistochemical features of two cases of apparently isolated arteritis of the epididymis are presented. The aetiology and pathogenesis of the condition are discussed. Immunoglobulin and complement were shown in the acute arterial lesions, but this is not conclusive evidence that isolated arteritis is either an immune complex disease or a forme fruste of polyarteritis nodosa.